Strategi Optimalisasi Social Media Marketing Melalui Instagram untuk Meningkatkan Penjualan pada Usaha Bakso Neng Ziya - Sudewa, Jaka; Nurwati, Ucu; Marlina Susana, Lina (Universitas Koperasi Indonesia, 2025)
This study aims to evaluate the effectiveness of the Social Media Marketing (SMM) strategy implemented through the Instagram account of Bakso Neng Ziya in increasing consumer appeal and purchase intention. The method used is the Importance Performance Analysis (IPA) approach, involving 60 respondents as the research sample. A total of 13 SMM indicators were analyzed based on two main dimensions: the level of importance and the level of performance from the consumers’ perspective. The results indicate an average conformity level of 72.92%, suggesting that the implementation of the strategy has not fully met customer expectations. Several key indicators were found in the main priority quadrant for improvement, such as posting consistency, visual content design, and audience engagement. Based on these findings, it is recommended that Bakso Neng Ziya enhance the quality of visual content, strengthen interaction with customers, and implement a regular evaluation system of social media performance to optimize the effectiveness of its digital marketing strategy. Keywords: Social Media Marketing, Instagram, Importance Performance Analysis, digital strategy, Bakso Neng Ziya